2012
DOI: 10.1016/j.cgh.2011.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the 2008–2009 Economic Recession on Screening Colonoscopy Utilization Among the Insured

Abstract: BACKGROUND & AIMS Economic factors might affect the use of recommended preventative services. We sought to determine whether the recent, severe economic recession was associated with diminished screening colonoscopy rates among an insured population and to assess the relationship between out-of-pocket (OOP) costs and screening colonoscopy use. METHODS Administrative data from 106 health plans (LifeLink™ Health Plan Claims Database) were analyzed to determine monthly rates of screening colonoscopies performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 38 publications
(41 reference statements)
4
32
1
Order By: Relevance
“…For example, it is not possible with this data to determine the extent to which the macroeconomic events impacted screening rates. Although prior reports have implicated the 2007 financial crisis as a contributor to the recent decline in screening, 66 our data suggest that less aggressive screening guidelines may have also played a role. This is consistent with an analysis from the Congressional Budget Office that concluded that a general slowing in Medicare FFS expenditure growth from 2007 to 2010 compared with 2000 to 2005 was mostly unexplained by recession effects, and that Medicare FFS health care utilization is largely independent of personal wealth.…”
Section: Discussioncontrasting
confidence: 57%
“…For example, it is not possible with this data to determine the extent to which the macroeconomic events impacted screening rates. Although prior reports have implicated the 2007 financial crisis as a contributor to the recent decline in screening, 66 our data suggest that less aggressive screening guidelines may have also played a role. This is consistent with an analysis from the Congressional Budget Office that concluded that a general slowing in Medicare FFS expenditure growth from 2007 to 2010 compared with 2000 to 2005 was mostly unexplained by recession effects, and that Medicare FFS health care utilization is largely independent of personal wealth.…”
Section: Discussioncontrasting
confidence: 57%
“…28 Indeed, 500,000 fewer screening colonoscopies were performed among adults aged 50–64 years during the recession than would have been expected based on trends before the recession. 29 Downstream economic effects of the recession may have also affected patients’ willingness to see providers and ability to afford (expensive) colonoscopy copayments. Around the same time, health care reform emphasized high-value care and penalized unnecessary medical tests and procedures.…”
Section: Declining Colonoscopy Rates After the Economic Recessionmentioning
confidence: 99%
“…5 Consistent with prior recessions in American history, these economic shifts resulted in a reduction in health services utilization among the general population. 1 , 5 , 6 , 7 …”
Section: Introductionmentioning
confidence: 99%